Science, innovation and society entailment: experiences of the Minimal Access Surgery National Center - Rosalba Roque González; Vivianne Maria Anido Escobar; Antonia Remigio Montero (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The link between science and innovation is not only considered in the introduction of new products and services by the hospitals, but also as a wide range of actions, which include healthcare management activities, related to the educational process and focused on turning knowledge into the foundation of the economic growth and the increased quality of life of the population. Objective: To present the experience of the Center for Minimal Access Surgery as an entity of science and technological innovation of the Ministry of Public Health and Center of Postgraduate Studies of the University of Medical Sciences of Havana, as well as the scientific, technical and social benefits that this experience has provided to the Cuban population. Material and Methods: The following techniques are used: participative observation: content analysis of documents and teamwork. Results: The analysis carried out comprises three main stages: Seed (1980-1992); Foundation (1993-2004) and Consolidation (2005-Present). Nowadays, the Center is a consolidated healthcare institution, oriented towards the excellence in its management practices. Conclusions: Throughout its history, the Center has reached significant scientific achievements and has contributed to society while fulfilling its mission, which integrates healthcare, teaching and research, constituting one of the most important achievements in the Cuban medicine and a clear example of how it is possible to strengthen the link between science and innovation by means of multiple strategies. Keywords: Minimal access surgery, science, innovation, health services, society, National Center.